Students' feelings in higher education: A first investigation in Italy with the University Students Belonging Scale - Marina Galioto; Ivan Giuseppe Cammarata; Marirosa Fortunato Priore; Paula Tavares; Stefano Boca; Cinzia Novara; Gioacchino Lavanco; Antonino Bianco (Social Sciences and Humanities Open)
Promoting students' sense of belonging is becoming a priority in higher education environments owing to its multiple benefits for academic life.Using the University Students Belonging Scale (USBS), this research aims to explore how this feeling is rated by students who attend two groups of programs inside the Department of Psychology, Educational Science and Human Movement from the University of Palermo, one of the biggest universities in Southern Italy. Merging all the courses from departmental Social Sciences degrees in one as the Psychology and Educational Sciences (PES) program, we compared this to the courses from departmental Sport and Exercise Sciences degrees, represented as the Sport Exercise Sciences (SES) program.We gathered 201 replies to the questionnaire and found that students coming from SES showed a higher level of sense of belonging, both in cumulative scale and subscales. Furthermore, analyzing scores among the subscales, we found that students expressed higher satisfaction in relation to items evaluating the perception of self-identity within the academic context on one hand and in relation to evaluating the quality of the relationship with peers and professionals on the other hand. In our understanding, institutional environment and social relations with academics and staff play a central role in the way they make students feel engaged and cared, correspondingly affecting motivation and academic performance. Future research on the topic should consider feasible strategies for implementing interventions to enhance overall well-being and sense of belonging in the university; in parallel, further investigations should be able to explain the reasons underlying the differences in the groups' feelings.